(untitled) (Pubmet, 2022)
Introduction. During the COVID-19 pandemic, our research and development team at the Croatian Academic and Research Network (CARNET) studied the implementation of distance learning, and here we present our methodological approach which is focused on communication supported by digital technologies. Our method combines quantitative and qualitative approach, the first by means of an online questionnaire on a large sample of respondents consisting of 535 principals, 5,619 teachers and 20,717 parents (26,871 in total). The qualitative part was carried out with eleven participants: five teachers, three principals, and three pedagogues, who kept reflective diaries (logs, journals) about what they were doing and why (Turner, 2020) and participated in communities of practice (Wenger, 1998) and individual interviews. The objectives of the qualitative research were to: ▸ gain insight into the practices of using technology in distance learning, ▸ provide support to teachers, principals, and pedagogues to study their own practice and give recommendations for further possible distance learning. Their testimonies describe each situation without the intervention of external researchers and provide researchers with insight into the actual practices of educators – participants / researchers (Meth, 2003). Communication as a prerequisite and result of a qualitative approach Throughout the writing phase of the research diaries, the coordinator closely collaborated with researchers who shared their experiences via weekly online meetings, e-mail, telephone. We also held 13 focus groups with the researchers. Communication of all involved was a prerequisite but also the result of the research. Due to its importance, we determined a communication strategy and selected the most efficient communication channels in advance, so that they did not require additional mastering of communication tools for video conferencing. Likewise, the pace and time of the meeting was measured so as not to further burden the researchers, who were primarily focused on writing diaries. This qualitative research resulted in more than 220 pages of diary entries and established two communities of practitioners – one consisting of pedagogues and principals and the other of teachers, who were meeting separately every two weeks. In addition, the research included dozens of hours of individual interviews. Conclusion. Qualitative action research is based on communication between researchers, and if it is designed that way, between researchers and the research coordinator. In an online environment, communication needs to be planned and rely on the digital tool that will be used and on the dynamics of interactions.